Percutaneous Selective Vertebroplasty: State of the Art Management in Well-Confined Metastatic Vertebral Lesions - Elnoamany, Hossam (Asian Spine J, 2016)
STUDY DESIGN: Prospective cohort study. PURPOSE: To evaluate the clinical and radiological results of percutaneous selective vertebroplasty (PSV) as first-line treatment options in the setting of well-confined spinal metastases. OVERVIEW OF LITERATURE: Recent technological advances combined with innovative interventional techniques enable an alternative less invasive treatment option for many patients with malignant vertebral body infiltration. Percutaneous vertebral augmentation procedures offer less invasive but effective pain relief to many patients with symptomatic spinal metastatic disease. METHODS: Eleven patients with 21 well-confined metastatic vertebral lesions that had been treated with PSV were included. Pain was evaluated one week, one month, 3 months and 6 months post-procedure using a 10-point visual analogue scale (VAS). A statistical analysis including repeated measures analysis of variance test was used to collectively indicate the presence of any significant differences between different time sequences. Medication usage and range of mobility were also evaluated. RESULTS: The 11 patients had an average age of 42 years and 54.5% were male. Highly significant improvements in VAS scores at rest and with activity (p<0.001) were evident. There was a significant decrease in rate of medication consumption post-procedure (p<0.05). CONCLUSIONS: PSV can be used successfully as the first-line treatment for well-confined metastatic vertebral lesions. It is also an effective method to decrease pain, increase mobility, and decrease narcotic administration in such patients.